Implementation of long-term care for older adults: a literature review - Prihatama, Rizky Putra; Ah Yusuf (Journal of the Pakistan Medical Association, 2023)
Objective: To explore the abuse and neglect phenomenon in long-term care facilities for the elderly population. Method: The systematic review comprised search on PubMed, CINAHL, MEDLINE and ScienceDirect databases following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The key words used were older people care, long-term care, older people and older adults. Articles published in the last 5 years between 2017 to 2021 in recognised English-language journals and whose full text was available on the websites were included. Details of the selected studies were noted and analysed. Results: Of the 336 studies initially identified, 15(4.46%) were reviewed in detail. Of them, 3(20%) had been done in North America, 6(40%) in Europe and 6(40%) in Asia. The prevalence of abuse and neglect in long-term care facilities for the elderly was generally high, with nursing home staff mostly involved due to burnout syndrome or related to personal factors, such as childhood adversity and work-related stress. Conclusion: Better understanding is critical for improving the quality of care in long-term care facilities to prevent abuse and neglect with the elderly. Keywords: Aged, Caregivers, Healthcare quality and services, Long-term care.